The Impact of Changes in Globalization of Life in Indonesia - Miftahul Jannah Hasibuan; Nuri Aslami (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Globalization is the linkage and dependence between nations and between people around the world through trade, investment, travel, popular culture, and other forms of interaction so that the boundaries of a country become increasingly narrow. The formulation of the problem in writing this scientific paper is,